Osteopontin Splice Variants Differentially Exert Clinicopathological Features and Biological Functions in Gastric Cancer - Tang, Xiaojian (Ivyspring International Publisher, 2012)
Purpose: Gastric cancer (GC) remains a leading cause of death worldwide, and an elevated expression of osteopontin (OPN) may correlate with its poor survival. Alternative splicing of OPN can result in three isoforms, OPN-a, OPN-b and OPN-c. The aim of our current study is to examine the expression pattern and biological functions of OPN splice variants in GC. Methods: Firstly, we evaluated the expression of OPN splice variants in 7 gastric cell lines, 101 pairs of GC tissues and their adjacent non-tumor tissues by Quantative real-time PCR (QT-PCR). Gain-of-function experiments were subsequently performed to determine their diverse roles in malignant behaviors of GC. Besides, their differential effects on the regulation of crucial downstream molecules were further explored in the anti-apoptotic and pro-metastatic process. Results: We found that OPN-b is the dominant kind of OPN isoform in GC cell lines. Although the expression levels of three variants were all elevated in GC tissues, increased OPN-b or OPN-c expression could correlate with clinicopathological features. Functional analyses further showed that OPN-b most strongly promoted GC cell survival possibly by regulation of Bcl-2 family proteins and CD44v expressions. Moreover, OPN-c most effectively stimulated GC metastatic activity by increasing secretion of MMP-2, uPa, and IL-8. Conclusions: Our results suggest that OPN splice variants differentially exert clinicopathological features and biological functions in GC. Therefore, focusing on specific OPN isoform could be a novel direction for developing diagnostic and therapeutic approaches in GC.